Reconstruction of paleo river systems and distribution of sedimentary facies of Shanxi and lower Shihezi formations in southern Ordos basin - WANG, Chao-yong; WANG, Ze-cheng; WANG, Ji-lin; BAO, Yuan; HU, Xiu-mei (Journal of China University of Mining and Technology, 2008)
The study area is located in the south of Huanxian county, in Yan＇an and Puxian counties and to the north of Xi＇an. The Shanxi and lower Shihezi formations are important gas-bearing formations. Given our analysis of the direction of rivers, the contents of stable heavy minerals and of feldspar of palaeo river systems, the study area is divided into six palaeodrainage patterns corresponding to six feldspar regions and six sedimentary facies regions. On this basis, the distribution of sedimentary facies was also analyzed. During the Shanxi stage, a delta front was deposited in the Huanxian region and delta plains and fronts were deposited in the Pingliang, Chunhua-Yaoxian and Hancheng-Chengcheng regions. In the Yan＇an-Daning region, only a delta front was developed. The distribution of sedimentary facies in the earlier Shihezi stage originated from the Shanxi stage. A delta front was developed in the Huanxian region while a delta plain and front developed in the Pingliang-Zhenyuan region during the same time. Lakes originated only in the Zhenyuan-Huanxian-Huachi-Zhengning and Daning-Jixian zones. This analytical method shows that different palaeodrainage patterns can be effectively distinguished in order to forecast sedimentary facies.